From diffuse intrinsic pontine glioma to diffuse midline glioma H3K27M-altered: What has been the role of stereotactic biopsy? - RANC, Revista Argentina de Neurocirugia; Becerra Castro, María Victoria; Alamar Abril, Mariana; Culebras Palau, Diego; Candela Cantó, Santiago; Morales La Madrid, Andrés; Hinojosa Mena-Bernal, José (Revista Argentina de Neurocirugía, 2024)
Background: several clinical studies have demonstrated the safety and feasibility of stereotactic biopsy in the setting of Diffuse Intrinsic Pontine Glioma (DIPG) and have contributed to a deeper understanding of the molecular biology of this disease. These developments led to look into in other lines of treatment, based on individualized approach modality and clinical trials, in a disease with no cure and therefore fatal prognosis. However, for many years, the role of the biopsy has been a topic of debate and controversy. Objective: to perform a historical review about the surgical perception of stereotactic biopsy in DIPG, in addition to contributing to a better knowledge and comprehension of its molecular biology, and consequently, the impact in innovative therapeutic options. Methods: characteristic clinical symptoms and pathognomonic radiographic features of DIPG are described. Limitations and consequences of classic diagnosis are analyzed, as well as its impact on their treatment. Results: a historical vignette about the role of stereotactic biopsy in brainstem tumors and in DIPG is elaborated, along with its impact on new developments of molecular pathophysiology for these tumors and novel treatment approaches. Conclusion: stereotactic biopsy in diffuse intrinsic pontine glioma is a feasible and safe procedure with low morbidity and mortality rate and high diagnostic yield. However, performing DIPG biopsy is recommended to be carried out in experienced and reference medical centers in pediatric neuro-oncology.